Breakthrough - Book 1 - Grumley, Michael C. ([United States] : [Michael C. Grumley], 2013)
Deep in the Caribbean ocean, a nuclear submarine is forced to suddenly abort its mission under mysterious circumstances. Strange facts begin to emerge that lead naval investigator John Clay to a small group of marine biologists who are quietly on the verge of making history. Alison Shaw and her team are preparing to translate the first two-way conversation with another animal species, but they are about to discover much more than they ever expected. When a mysterious object is found on the ocean floor and an unknown group suddenly becomes interested in her work, Alison learns that Clay may be the only person she can really trust. Together they find themselves embroiled in a desperate attempt to stop a catastrophe that spans the Atlantic Ocean and reaches all the way to Antarctica.
Keywords: United States. -- Navy -- Fiction; Human-animal communication -- Fiction; Action and adventure fiction; Thrillers (Fiction); Science fiction